OtagoNet: One region's model for virtual schooling - Keryn Pratt; Ken Pullar (Flexible Learning Association of New Zealand, 2013)
Virtual schools are increasingly common in New Zealand and internationally as schools are challenged to meet the needs of their students. This case study presents an overview of a model used by a group of schools in rural Otago, New Zealand known as OtagoNet and the research conducted to evaluate this model. This OtagoNet group of schools have been using videoconference to deliver classes to each other's students since 2002. The leadership team and roles are described, and the funding model, which is based on reciprocity, is outlined. The most common teaching and learning practices are described, and support mechanisms identified. Finally, a summary of the research conducted since OtagoNet's inception is presented. This research shows that this model is generally effective for teachers and learners, although a number of factors impact on this.